Evaluation of Ergonomic Risks in Labour-Intensive Remanufacturing Tasks - Aravindakshan, Harikrishna Menon; Vettiyattil Sasikumar, Karthik (My University, 2026)
Remanufacturing is an important circular economy strategy that prolongs product life and lowers the consumption of virgin raw materials, thereby offering both economic and environmental benefits for companies. However, the process remains labour-intensive because cores arrive in varying states of wear and damage, which creates challenges for operators during their tasks.This study aims to analyse and evaluate the ergonomic risks associated with a labour-intensive remanufacturing workstation by applying ergonomic assessment methods. A mixed-methods approach was adopted, combining theoretical insights from the literature, semi-structured interviews with industry and academic experts, and a simulation-based analysis with ergonomic evaluations using the Rapid Entire Body Assessment (REBA) method and a separate Key Indicator Method (KIM) assessment. Based on the findings from the semi-structured interviews, the disassembly workstation was selected for the simulation-based ergonomics analysis. Three scenarios were modelled and evaluated with REBA in the simulation, while KIM was applied independently to determine the physical workload.The analysis suggests that the disassembly process presents significant ergonomic challenges. Identified risks include awkward body postures, high force exertions, repetitive movements, limited accessibility, and the handling of heavy components. The REBA assessment indicated a moderate ergonomic risk for all three postures studied, whereas the KIM results showed higher physical workload for the bolt removal and trolley transportation tasks. The results indicate that digital simulation combined with ergonomic evaluation tools such as REBA and KIM can effectively identify high-risk activities within remanufacturing workstations.
Keywords: Remanufacturing; Labour-intensive Workstation; Ergonomics; Ergonomic Assessment methods; Manual Disassembly